2020
DOI: 10.32801/lamlaj.v5i1.140
|View full text |Cite
|
Sign up to set email alerts
|

Development of Indonesian Sharia Banks with Malaysia Comparation Method (Study of History, Products and Legal Assets)

Abstract: Sharia banking is developed in response to economic and cultural groupsthat are used to accommodate those who want the services to be carried out withIslamic sharia principles and morals. The development of Sharia banks in Indonesiaand Malaysia needs to be studied more deeply because Malaysia first establishedSharia banks in 1983 through Bank Islam Malaysia Berhad (BIMB) while the firstsharia bank in Indonesia, which named Bank Muamalat, was burned in 1991, whichdetermines the direction of the progress of shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The fourth hypothesis proposed in this study has been successfully verified, so the attitude of the MSME owners has an effect on the intention to use sharia cooperative products. In a study conducted by various researchers in the field of Islamic finance (Albashir et al, 2018;Berakon et al, 2022;Dzuljastri Abdul Razak and Muhamad Abduh, 2012a;Hendrik et al, 2018;Hutomo Mukti, 2020;Jaffar & Musa, 2014, 2016Rokhman & Abduh, 2020;Shabrina et al, 2018;Vidia Khairunnisa & Hendratmi, 2019), researchers revealed that attitude is a significant determinant of intention. The results obtained in this study are analogous to the results of the previous studies above.…”
Section: Results Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth hypothesis proposed in this study has been successfully verified, so the attitude of the MSME owners has an effect on the intention to use sharia cooperative products. In a study conducted by various researchers in the field of Islamic finance (Albashir et al, 2018;Berakon et al, 2022;Dzuljastri Abdul Razak and Muhamad Abduh, 2012a;Hendrik et al, 2018;Hutomo Mukti, 2020;Jaffar & Musa, 2014, 2016Rokhman & Abduh, 2020;Shabrina et al, 2018;Vidia Khairunnisa & Hendratmi, 2019), researchers revealed that attitude is a significant determinant of intention. The results obtained in this study are analogous to the results of the previous studies above.…”
Section: Results Interpretationmentioning
confidence: 99%
“…below.Source:Albaity & Rahman, 2019;Hutomo Mukti, 2020;Lechner & De Vries, 1995a;Nugroho et al, 2017a; Rahman et al, Figure 1. Research Model Framework …”
mentioning
confidence: 99%
“…The development of digital banking has had a positive impact since it was first launched. This can be proven by the increasing number of transactions using mobile banking reaching 158% from 2018 to 2023 25 . Therefore, many banks are making digital banking a strategy to get more consumers.…”
Section: Digital Banking Services At Bank Syariah Indonesiamentioning
confidence: 99%
“…Islamic banking institutions have the advantage of sharia principles and the realization of Islamic economic values in all banking operations that prioritize customer satisfaction and welfare, while still generating commercial profits for Islamic banks. In addition, the diversification of advantages can also be seen in the prohibition of transactions that are not in accordance with Islamic law as performed by conventional banks (Hutomo Mukti, 2020).…”
Section: Introductionmentioning
confidence: 99%